Guide :

# HOW DO U COMBINE THE LIKE TERMS

8X SQUARE + 6X TO THE THIRD POWER +2x +5X 3X+&X SQUARE + 9X 4XTO THE THIRD POWER + 9X +2X (5xSQUARE +6X+8)+(6XTO THE THIRD POWER+2xSQUARE-4X) (10XTO THE THIRD POWER +6XSQUARE+4X)-(8XTO THE THIRD POWER+2XSQUARE-3X)

## Research, Knowledge and Information :

### Combining Like Terms Lessons | Wyzant Resources

What Does Combining Like Terms Do? ... Equations that require you to combine like terms before solving the equation. Equation Calculator

### How to Combine Like Terms: 3 Steps (with Pictures) - wikiHow

How to Combine Like Terms. Combining like terms is one of the most important skills to master in Algebra. Without knowing how to combine like terms, it is impossible ...

### How to Combine Like Terms in Math. To Combine Like terms all ...

How to Combine Like Terms. Rules for Combing Like Terms. Algebra ; Geometry ; Trigonometry; ... 2x 2 and x 2 are like terms so you can combine (ie 'add') them to ...

### Polynomials: Combining "Like Terms" - Purplemath

Defines 'like terms' and demonstrates how to combine like terms. Warns against common student mistakes. ... So if you have something like x 3 + x 2, ...

### Combining Like Terms - Free Math Help

Combine Like Terms. ... Combining like terms enabled you to take that huge mess of an equation and make it into something much more obvious.

### Combining like terms (video) | Khan Academy

Combining like terms with distribution. Practice: Combining like terms with distribution. Next tutorial. The distributive property. Tags. Combining like terms. Video ...

### Combining Like Terms Practice - Math Is Fun

"Like Terms" It may help you to read Introduction to ... In other words, terms that are "like" each ... Combining Like Terms. You can add like terms together to ...

### Combining like terms (practice) | Khan Academy

Khan Academy is a nonprofit with the mission of providing a free, ... Practice: Combining like terms with distribution. Next tutorial. The distributive property.

### Algebra Basics - Evaluating expressions - First Glance

... like terms are terms that contain the ... Since adding or subtracting unlike terms is like mixing ... only like terms can be combined. To combine like ...

### Simplfy an Algebraic Expression by Recognizing Like Terms ...

Simplfy an Algebraic Expression by Recognizing Like ... Algebraic Expression by Recognizing Like Terms ... will show you how to identify and combine like terms.

## Suggested Questions And Answer :

### (13-3)x5=50

Simplifying x + 2 = 3x + -1x2 + 5 Reorder the terms: 2 + x = 3x + -1x2 + 5 Reorder the terms: 2 + x = 5 + 3x + -1x2 Solving 2 + x = 5 + 3x + -1x2 Solving for variable 'x'. Reorder the terms: 2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: 2 + -5 = -3 -3 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: x + -3x = -2x -3 + -2x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Reorder the terms: -3 + -2x + x2 = 5 + -5 + 3x + -3x + -1x2 + x2 Combine like terms: 5 + -5 = 0 -3 + -2x + x2 = 0 + 3x + -3x + -1x2 + x2 -3 + -2x + x2 = 3x + -3x + -1x2 + x2 Combine like terms: 3x + -3x = 0 -3 + -2x + x2 = 0 + -1x2 + x2 -3 + -2x + x2 = -1x2 + x2 Combine like terms: -1x2 + x2 = 0 -3 + -2x + x2 = 0 Factor a trinomial. (-1 + -1x)(3 + -1x) = 0 Subproblem 1 Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1 Subproblem 2 Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3 Solution x = {-1, 3}

### (8x)[(2x)^-2=8

Simplifying 8x = 2x2 + 8 Reorder the terms: 8x = 8 + 2x2 Solving 8x = 8 + 2x2 Solving for variable 'x'. Reorder the terms: -8 + 8x + -2x2 = 8 + 2x2 + -8 + -2x2 Reorder the terms: -8 + 8x + -2x2 = 8 + -8 + 2x2 + -2x2 Combine like terms: 8 + -8 = 0 -8 + 8x + -2x2 = 0 + 2x2 + -2x2 -8 + 8x + -2x2 = 2x2 + -2x2 Combine like terms: 2x2 + -2x2 = 0 -8 + 8x + -2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-4 + 4x + -1x2) = 0 Factor a trinomial. 2((-2 + x)(2 + -1x)) = 0 Ignore the factor 2. Subproblem 1 Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2 Subproblem 2 Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2 Solution x = {2, 2}

### Guys can you help me solve these following equations

This should help: Simplifying 3p + -1 = 5(p + -1) + -2(7 + -2p) Reorder the terms: -1 + 3p = 5(p + -1) + -2(7 + -2p) Reorder the terms: -1 + 3p = 5(-1 + p) + -2(7 + -2p) -1 + 3p = (-1 * 5 + p * 5) + -2(7 + -2p) -1 + 3p = (-5 + 5p) + -2(7 + -2p) -1 + 3p = -5 + 5p + (7 * -2 + -2p * -2) -1 + 3p = -5 + 5p + (-14 + 4p) Reorder the terms: -1 + 3p = -5 + -14 + 5p + 4p Combine like terms: -5 + -14 = -19 -1 + 3p = -19 + 5p + 4p Combine like terms: 5p + 4p = 9p -1 + 3p = -19 + 9p Solving -1 + 3p = -19 + 9p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-9p' to each side of the equation. -1 + 3p + -9p = -19 + 9p + -9p Combine like terms: 3p + -9p = -6p -1 + -6p = -19 + 9p + -9p Combine like terms: 9p + -9p = 0 -1 + -6p = -19 + 0 -1 + -6p = -19 Add '1' to each side of the equation. -1 + 1 + -6p = -19 + 1 Combine like terms: -1 + 1 = 0 0 + -6p = -19 + 1 -6p = -19 + 1 Combine like terms: -19 + 1 = -18 -6p = -18 Divide each side by '-6'. p = 3 Simplifying p = 3

### 1/4x^5-3+1/2x^5-6x-35 how do you combine like terms with this problem

Combining like terms means adding or subtracting the coefficients of terms that have the same variables. x^2 can only be combined with x^2, x^4 with x^4, and so on. In your problem, you have two terms that have an x^5 and two terms that have no variable, so you would combine the two x^5 terms and then you would combine the two non x terms. An example: 7x^2 + 3 - 4x^2 + 5x + 2 7x^2 and -4x^2 are like terms. 3 and 2 are like terms. 5x has no like terms so it just stays the same.  7x^2 - 4x^2 = 3x^2  and 3 + 2 = 5   and 5x = 5x So the answer would be    3x^2 + 5x + 5

### Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Factor a trinomial. (-9 + -1x)(2 + -3x) = 0 Subproblem 1 Set the factor '(-9 + -1x)' equal to zero and attempt to solve: Simplifying -9 + -1x = 0 Solving -9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -1x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1x = 0 + 9 -1x = 0 + 9 Combine like terms: 0 + 9 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9 Subproblem 2 Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667 Solution x = {-9, 0.6666666667}

### how do you combine like terms with the same variable?

Like terms are where the exponents and the variable are the same but the coefficients may be different. Constants are all considered to be like terms. The same variable with different exponents can only be combined by factorisation, the variable with the lowest exponent usually being a common factor. Factorisation can also be used when two coefficients have a common factor. You can't combine different variables, even if they have the same exponent. Factorisation can be used when you have products of different variables. EXAMPLE 16+3x^3+5x^2+2x^3-y^2-x+4y+8x+y+6y^2-2x+9-25 can be simplified: x^3 term: 3x^3+2x^3 is 5x^3 x^2 term: 5x^2 only y^2 term: -y^2+6y^2 is 5y^2 x term: -x+8x-2x is 5x y term: 4y+y is 5y constant: 16+9-25 is 0 So we have: 5x^3+5x^2+5y^2+5x+5y. But 5 is a common factor: 5(x^3+x^2+y^2+x+y). Further factorisation is possible but looks clumsy: 5(x(x^2+x+1)+y(y+1))

### how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0 Subproblem 2 Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4 Subproblem 3 Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1 Solution x = {0, -4, 1}

### Solve 6-(5r)=5r-3, 12p-7=3p+8, 10(-4+y)=2y, -(8n-2)=3+10(1-3n), and 1/4(60+165)=15+45

1). 6 - (5r) = 5r - 3     6 -5r = 5r - 3 (distribute the negative)        -5r = 5r - 3 - 6 (subtract 6 from both sides)      -10r = -9 (subract 5r from both sides and combine like terms)           r = -9/-10 (divide by -10 on both sides)           r = 9/10 (negative divided by negative = positive) 2). 12p - 7 = 3p + 8            12p = 3p + 8 + 7 (add 7 to both sides)     12p - 3p = 15 (subtract 3p from both sides and add like terms)              9p = 15 (combine like terms on left)                p = 15/9 (divide both sides by 9) 3). 10 (-4 + y) = 2y        -40 + 10y = 2y (distribute the 10)                  10y = 2y + 40 (add 40 to both sides)           10y - 2y = 40 (subtract 2y from both sides)                    8y = 40 (combine like terms)                      y = 5 (divide both sides by 8) 4). -(8n - 2) = 3 + 10(1 - 3n)        -8n + 2 = 3 + 10 - 30n  (distribute)              -8n = 3 + 10 - 30n - 2 (subtract 2 from both sides)    -8n + 30n = 3 + 10 - 2 (add 30n to both sides)              22n = 11 (combine like terms)                  n = 11/22 (divide each side by 22)                  n = 1/2 (simplify) 5).        1/4(60 + 165) = 15 + 45      1/4(60) + 1/4(165) = 15 + 45 (distribute 1/4 to numbers inside ())               60/4 + 165/4 = 60 (combine numbers on right)                           225/4 = 60 (add fractions together)                                  0 = 60(4/4) - 225/4 (subtract 225/4)                                  0 = 240/4 - 225/4 (find common denominator)                                  0 does not equal 15/4 (subtract)                                  impossible. (impossible to solve)

### How do you solve (18x+1) + (4x-2x) = 140

Simplifying 2x + 140 = 4x + 16 Reorder the terms: 140 + 2x = 4x + 16 Reorder the terms: 140 + 2x = 16 + 4x Solving 140 + 2x = 16 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 140 + 2x + -4x = 16 + 4x + -4x Combine like terms: 2x + -4x = -2x 140 + -2x = 16 + 4x + -4x Combine like terms: 4x + -4x = 0 140 + -2x = 16 + 0 140 + -2x = 16 Add '-140' to each side of the equation. 140 + -140 + -2x = 16 + -140 Combine like terms: 140 + -140 = 0 0 + -2x = 16 + -140 -2x = 16 + -140 Combine like terms: 16 + -140 = -124 -2x = -124 Divide each side by '-2'. x = 62 Simplifying x = 62